IMPLEMENTASI MODEL DISCOVERY LEARNING DALAM UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA - Jafri Haryadi; Santi Pratiwi (Universitas Islam Sumatera Utara, 2021)
This study aims to determine the increase in active activity and student learning outcomes through discovery learning models in the physics learning process. This study applies a classroom action research model that is implemented to correct some weak aspects of previous learning through a process of reflection. The object of this research is the students of SMA Negeri 2 Perbaungan class X, amounting to 30 people. The results indicated that there had been a significant increase in student activity and learning completeness. In the first cycle, the percentage of student activity was 46.30% and the percentage of student learning completeness was 40%. As for the second cycle, it was found that the average student activity was 77.67% and the percentage of student learning completeness was 86.67%. This shows that the activities that have been carried out in each cycle II do not need to be corrected and declared successful.